Actively Q-Switched Tm:YAP Laser Constructed Using an Electro-Optic Periodically Poled Lithium Niobate Bragg Modulator - Shou-Tai Lin; Zhao-Ren Qiu; Cheng-Po Chen (IEEE Photonics Journal)
We present an EO Q-switched Tm:YAP laser constructed with a periodically poled Mg-doped congruent lithium niobate (PPMgCLN) Bragg modulator. A 2-mm-thick PPMgCLN modulator was adopted, and the internal stress generated in the electric poling process was released by annealing. The peak stress-induced refractive index variance for e-wave was deduced to be 2.29 × 10−5 at 1064 nm. When the absorbed pump power and repetition rate were 13.4 W and 1 kHz, respectively, the laser had a Q-switched pulse energy of 2 mJ, a pulse duration of 60 ns, and a peak power of 33.3 kW. By varying the reflection of the output coupler, output wavelengths of between approximately 1985 and approximately 1940 nm can be selected, making this laser a potential tool for pumping mid-IR sources and biomedical applications.